2007
DOI: 10.1101/gr.6533407
|View full text |Cite
|
Sign up to set email alerts
|

Human gene organization driven by the coordination of replication and transcription

Abstract: In this work, we investigated a large-scale organization of the human genes with respect to putative replication origins. We developed an appropriate multiscale method to analyze the nucleotide compositional skew along the genome and found that in more than one-quarter of the genome, the skew profile presents characteristic patterns consisting of successions of N-shaped structures, designated here N-domains, bordered by putative replication origins. Our analysis of recent experimental timing data confirmed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
207
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(222 citation statements)
references
References 44 publications
15
207
0
Order By: Relevance
“…In mammals, gene order conservation has been associated with the regulation of gene expression (Semon and Duret, 2006;Gierman et al, 2007), replication, and chromatin structure (Huvet et al, 2007). Nonrandom patterns of gene expression are found among proximally located rice (Ma et al, 2005) and Arabidopsis (Ren et al, 2007) genes.…”
Section: Distinguishing Features Of the Cerealsmentioning
confidence: 99%
“…In mammals, gene order conservation has been associated with the regulation of gene expression (Semon and Duret, 2006;Gierman et al, 2007), replication, and chromatin structure (Huvet et al, 2007). Nonrandom patterns of gene expression are found among proximally located rice (Ma et al, 2005) and Arabidopsis (Ren et al, 2007) genes.…”
Section: Distinguishing Features Of the Cerealsmentioning
confidence: 99%
“…It has been proposed that origins of replication lie frequently between promoters of active genes (MacAlpine and Bell 2005;Huvet et al 2007), which would make transcription and replication fork progression co-oriented ). Furthermore, transcription and replication are thought to be coordinated in the nucleus (Schwaiger and Schü beler 2006;Aladjem 2007) to be spatially and temporally separated.…”
Section: H4k16 Acetylation Links Chromatin With Early Replication Andmentioning
confidence: 99%
“…These four main chromatin states were further shown to correlate with MRT, namely from early to late replicating, a transcriptionally active euchromatin state (C1) enriched in insulator binding protein CTCF, a polycomb repressed facultative heterochromatin state (C2), a silent heterochromatin state (C3) not enriched in any available marks and a HP1-associated heterochromatin state (C4). When mapping these chromatin states inside the megabase-sized U-domains Audit et al 2012Audit et al , 2013, where the MRT is U-shaped and its derivative Nshaped like the nucleotide compositional asymmetry in the germline skew N-domains (Brodie of Brodie et al 2005;Touchon et al 2005;Audit et al 2007;Huvet et al 2007;Audit et al 2009;Baker et al 2010;Chen et al 2011;, we have shown that in these replication domains that cover about 50% of the human genome, the replication wave ) proceeds along a directional path through the four chromatin states, from the open euchromatin state C1 at U/N-domain borders successively followed by the three silent chromatin states C2, C3 and C4 at the U/N-domain centers . The complete analysis, of the other half of the genome that is complementary to U-domains ) has confirmed the dichotomic picture proposed in early studies in mouse (Farkash-Amar et al 2008;Hiratani et al 2008Hiratani et al , 2010 and human (Desprat et al 2009;Ryba et al 2010;Yaffe et al 2010) genomes, where early and late replicating regions occur in separated compartments of open and closed chromatin, respectively.…”
Section: Introductionmentioning
confidence: 99%